Burnout? A Study of a Group of Professors of the Finance and Auditing Career - Araque-Salazar, María Cristina (2019)
This research analyses regarding the Burnout syndrome in a group of university professors hired part time and full time in the Finance and Audit Career, with the objective of identifying the existence of this psychosocial factor and the evidence in relation to the changes in their mood or health is was related to their working hours and the lack of time assigned to their family and personal life. Therefore, the study shows a relationship between the type of work university school engages and the burnout effects that can be considered psycho-social issue, anonymous surveys were conducted in order to research the variables involved in this problem, they are the combination of teaching, regular contact with students in order to support their educational needs, new added academic requirements additional, administrative and management tasks and research, which in sum take time away from the personal and family life of these faculty members. A descriptive analysis is proposed throughout this study that provides data about the particular characteristics of each professor, about their changes of emotional changes and/or symptomatology, where it was evidenced that the administration of personal and family time depended directly on tasks and responsibilities assumed with them. The results give data on the involvement of teachers in terms of their physical and emotional health that corroborate the approach to greater labor requirement more symptoms and ailments.